PENGARUH JENIS BIOAKTIVATOR DAN PEMBERIAN BIOCHAR TERHADAP PROSES PENGOMPOSAN SAMPAH ORGANIK - Fabela, Erica; Siswanto, Siswanto; Sasongko, Purnomo Edi (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Combining the right bioactivator and biochar dosage can speed up the process and increase the compost quality. Using compost in agriculture can reduce the excessive use of chemical fertilizers, improve soil health and crop yields, and contribute to overall agricultural sustainability. Methods: The research was conducted in March-August 2021 in Kemantren Village, Tulangan District, Sidoarjo Regency. Analysis activities were conducted at the Land Resources Laboratory, Faculty of Agriculture, UPN